2019
DOI: 10.1093/pm/pnz096
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Initial Intrathecal Drug Ratio for Refractory Cancer-Related Pain for Early Pain Relief. A Retrospective Monocentric Study

Abstract: Objective Intrathecal (IT) drug delivery has shown its efficiency in treating refractory cancer pain, but switching opioids from the systemic to the intrathecal route is a challenging phase. Moreover, associations are widely used and recommended. Few data deal with the initial dosage of each drug. Analyzing conversion factors and initial dosages used in intrathecal therapy seems essential to decreasing the length of titration and to delivering quick pain relief to patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 30 publications
0
12
0
5
Order By: Relevance
“…An observational study designed to evaluate the 11‐year results (2006–2017) of IDDSs for refractory pancreas cancer pain [91, 92] demonstrated that IDDS‐treated patients experienced 50%–75% reductions in mean pain levels. Ropivacaine was usually added as a first‐ or second‐line therapy.…”
Section: Non–radiation‐focused Therapiesmentioning
confidence: 99%
“…An observational study designed to evaluate the 11‐year results (2006–2017) of IDDSs for refractory pancreas cancer pain [91, 92] demonstrated that IDDS‐treated patients experienced 50%–75% reductions in mean pain levels. Ropivacaine was usually added as a first‐ or second‐line therapy.…”
Section: Non–radiation‐focused Therapiesmentioning
confidence: 99%
“…Recently Dupoiron et al retrospectively reviewed 220 cancer patients on IDD and their initial intrathecal dosing with a focus on the relative efficacy of different ratios of local anesthetic and opioid. The authors estimated an OME to IME ratio closer to 250:1 but in the setting of a more progressive local anesthetic dosing protocol and a quite prolonged inpatient titration phase (24). In 2007, Mercadante et al reported the use of the 100:1 oral-to-intrathecal ratio in 55 cancer patients using externalized intrathecal catheters to syringe or bulb pumps.…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study attempted to determine optimal initial dosing strategies for refractory cancer‐related pain by retrospectively comparing 220 patients experiencing early versus late pain relief following implantation of IDDS. The authors report differences in systemic opioid doses on the day of implantation between different groups but do not report overall change in systemic opioid dose despite looking for measures of success between the two groups including rate of 50% NRS decrease between days 0 and 7, length of hospital stay, and number of IT drug dose adjustments (27).…”
Section: Discussionmentioning
confidence: 99%